Chemical codes of sensory neurons innervating the guinea-pig adrenal gland - Heym, Christine; Braun, Birgitta; Klimaschewski, Lars Peter; Kummer, Wolfgang (Cell & tissue research, 1995)
Retrograde neuronal tracing in combination with double-labelling immunofluorescence was applied to distinguish the chemical coding of guinea-pig primary sensory neurons projecting to the adrenal medulla and cortex. Seven subpopulations of retrogradely traced neurons were identified in thoracic spinal ganglia T1-L1. Five subpopulations contained immunolabelling either for calcitonin gene-related peptide (CGRP) alone (I), or for CGRP, together with substance (P (II), substance P/dynorphin (III), substance P/cholecystokinin (IV), and substance P/nitric oxide synthase (V), respectively. Two additional subpopulations of retrogradely traced neurons were distinct from these groups: neurofilament-immunoreactive neurons (VI), and cell bodies that were nonreactive to either of the antisera applied (VII). Nerve fibres in the adrenal medulla and cortex were equipped with the mediator combinations I, II, IV and VI. An additional meshwork of fibres solely labelled for nitric oxide synthase was visible in the medulla. Medullary as well as cortical fibres along endocrine tissue apparently lacked the chemical code V, while in the external cortex some fibres exhibited code III. Some intramedullary neuronal cell bodies revealed immunostaining for nitric oxide synthase, CGRP or substance P, providing an additional intrinsic adrenal innervation. Perikarya, immunolabelled for nitric oxide synthase, however, were too few to match with the large number of intramedullary nitric oxide synthase-immunoreactive fibres. A non-sensory participation is also supposed for the particularly dense intramedullary network of solely neurofilament-immunoreactive nerve fibres. The findings give evidence for a differential sensory innervation of the guineapig adrenal cortex and medulla. Specific sensory neuron subpopulations suggest that nervous control of adrenal functions is more complex than hitherto believed.
Gesehen am 05.11.2025